Dark Humor in Films of the 1960s - Dixon, Wheeler Winston. author. aut Link
VIII, 102 p.
Keywords: Focusing on "dark" or black comedy films in the US and the UK, Wheeler Winston Dixon provides a comprehensive overview of a variety of films and filmmakers (Vanishing Point, Marcel Hanoun), whose work has largely been ignored, but whose influence and importance is clearly present.